CHILDREN IMITATION ON DAILY LANGUAGES FAMILY COUNSELING PERSPECTIVE - Razi, Astri Delia; Siregar, Mawardi; Zulkarnain, Zulkarnain (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2018)
Humans learn differently. One way humans learn is to imitate (imitation). A child will imitate both parents and learn their habits and behavior patterns. Humans will learn many behaviors and habits in the early phases of his life by imitating his parents, older brothers, brothers and relatives around him. The position of the family in the development of the child's personality is very dominant. The family is a "Training Center" for the cultivation of values. Therefore, the family as a model to be imitated by the child has a very important role, both in language and behavior. This study discusses the imitation of children against everyday language in the family in Gampong Teungoh Langsa City, Aceh. The purpose of this research is to examine; The process of imitation of children against everyday language in the family in Gampong Teungoh and Parents efforts in overcoming the negative daily language imitation in the family.